Analyzing the effects of COVID-19 Pandemic on the financial performance: a case study of the transportation and logistics companies in Malaysia / Ummi Aiman Rahid - Rahid, Ummi Aiman (2022)
Financial performance is very important to measure the company's financial condition. As the Covid-19 has spread around the world and makes many businesses need to stop their operation because of the restriction made by the government. Many businesses had been affected by this pandemic Covid-19. The transportation and logistics companies are also one of the industries in Malaysia that had been affected by this pandemic. Shen et al., (2020) stated that Covid-19 outbreak may have an impact on the performance of logistics firm. It is because the logistics firm offers services which involve the movement. storage and flows of goods to the consumer. Meanwhile the transportation company offer the transportation services for the people to go to the place that they want. So. the restriction of travelling and movement control order from the government of Malaysia given an impact on the performance of those companies. The purpose of this study is to focus on analyzing the effect of pandemic Covid-19 on the financial performance of the transportation and logistics industries in Malaysia. The duration to collect the data is about 4 years which are from 2018 until 2021. That data will be collected in quarterly basis as a secondary and quantitative data. It will be collected from various sources and which include in the previous research. The dependent variable for this study is Return on assets (ROA) that represent the finance performance of those companies from logistics and transportation industries. The independent variables are Revenue (REV). Firm Size (SIZ) and Leverage (LEV). The population that had been chosen is from the transportation and logistics industry that had been listed in Bursa Malaysia. There are about 35 transportation and logistics companies that have been listed in Bursa Malaysia. The sample size for this study is about 8 transportation and logistics companies out of 35 companies that had been listed.